¿Son stakeholders los consumidores? - De la Cuesta Rute, José María (Revista de Derecho, 2019)
The present work is directed towards the analysis of whether the currently growingconcern for the so-called consumers and users in the field of mercantile law coincides ornot with the also growing attention to entrepreneurial or corporate social responsibility.To this means applies what could be held as an “amplified notion” and a “restrictive orstrict notion” of consumer. None of these notions postulates that mercantile law has toecho entrepreneurial social responsibility, whose justification, on the other side, is morethan debatable. The consideration of consumers in a wide sense as stakeholders does notadd much to the correct economical concept of entrepreneur and competitive marketand it therefore does not add much to mercantile law, which by definition, refers to thoseeconomical phenomenon. A restrictive notion of consumer which could be identifiedwith the integrates in a group of stakeholders is not consistent with the system of marketeconomy neither is it necessary for institutions of mercantile law to comply with theirduties, nor, least of all to form a Law of consumption as a systematic judicial branch.
Keywords: consumer; stakeholder; mercantile law; entrepreneurial social responsibility; law of consumption